2004
DOI: 10.1177/153537020422900305
|View full text |Cite
|
Sign up to set email alerts
|

Extract of Perilla frutescens Enriched for Rosmarinic Acid, a Polyphenolic Phytochemical, Inhibits Seasonal Allergic Rhinoconjunctivitis in Humans

Abstract: Extract of Perilla frutescens enriched for rosmarinic acid, a polyphenolic phytochemical, suppresses allergic immunoglobulin responses and inflammation caused by polymorphonuclear leukocytes (PMNL) in mice. However, few placebo-controlled clinical trials have examined the efficacy and safety of polyphenolic phytochemicals for treatment of allergic inflammatory diseases in humans. The present study determined whether oral supplementation with rosmarinic acid is an effective intervention for patients with season… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
115
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 169 publications
(117 citation statements)
references
References 17 publications
1
115
0
1
Order By: Relevance
“…GC inhibits the function of infiltrating inflammatory cells and their recruitment into the nasal mucosa. GC inhibits the maturation, cytokine production, COX-2 expression, FcεRI expression, and mediator release of mast cells (Takano et al, 2004;Smith et al, 2002). We observed that JW inhibited IgE production, inflammatory cytokine production, chemokine production, and COX-2 expression in the mice AR model.…”
Section: Discussionmentioning
confidence: 68%
“…GC inhibits the function of infiltrating inflammatory cells and their recruitment into the nasal mucosa. GC inhibits the maturation, cytokine production, COX-2 expression, FcεRI expression, and mediator release of mast cells (Takano et al, 2004;Smith et al, 2002). We observed that JW inhibited IgE production, inflammatory cytokine production, chemokine production, and COX-2 expression in the mice AR model.…”
Section: Discussionmentioning
confidence: 68%
“…The presence of rosmarinic acid (RA) in medicinal plants, herbs and spices, has been generated healthy and beneficial effects. Among these were several RA biological activities, including antioxidant, astringent, anti-inflammatory, antimicrobial, antiangiogenic, antiviral, antirheumatic, antiallergic, antidepressant, antidiabetic, and antitumor [2][3][4][5][6][7][8][9][10][11][12][13] . However, reports on its activity in the cardiovascular system are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…studies have been conducted on the compounds contained in perilla that have anti-infl ammatory 6,7 , anti-HIV-1 8 , antiallergic 9,10 , and anti-tumor 11,12 properties. Nonetheless, the antioxidant activity of perilla remains poorly understood.…”
mentioning
confidence: 99%